DETEKSI GEN MSG UNTUK PENINGKATKAN KETEPATAN DIAGNOSIS PNEUMOCYSTIS JIROVECII PADA PASIEN HIV DENGAN PNEUMONIA - Tjampakasari, Conny Riana; Yasmon, Andi; Sudarmo, Fitrahwati (Indonesian Journal of Biotechnology and Biodiversity, 2018)
AbstractPneumocystis jirovecii is the cause of opportunistic infections in the lower respiratory tract of immunocompromised patients, especiallyin human immunodeficiencyvirus (HIV). Until now the case of P. jirovecii in Indonesia is not known with certainty because the data obtained only based on patient’s clinical condition. Culture is still on going research while microscopic as a gold standard has some limitation, among others, takes a long time in the process, requires special kills to work and interpret results. The diagnosis of P.jirovecii infection in Indonesia is still based on clinical and microscopic examination, which takes a long time, is less sensitive and specific. Based on this reason then developed rPCR that  more sensitive and specific. In addtionthe results obtained are less sensitive and spesific. Based on that, in this study developed real-time PCR (rPCR) molecular test that more sensitive and apesific using gene MajorSurface Glicoprotein (MSG). MSG is detection target of its presence in the fungus cell wall is very abundant and has a sustainable sequence. The rPCR was successfully optimized with a minimum DNA detection capability of 6.55 cop / μl and did not cross-react with other microorganisms tested in this study. Obtauned 50 clinical sampels consisting of sputum and sputum induction. The result of comparison between microscopic test and rPCR show that rPCR increase positive results up to 20%. The rPCR test can detect P.jirovecii on clinical samples of sputum and induced sputum from HIV patients with pneumonia with CD4 +> 200 or ≤ 200 cells.  Keywords : real time PCR, HIV, pneumocystis jirovecii. AbstrakPneumocystisjiroveciiadalah penyebab infeksi oportunistik di saluran pernapasan bawah pada individu dengan sistem kekebalan tubuh yang lemah, terutama pada pasien HIV. Pemeriksaan infeksi P. jirovecii di Indonesia masih berdasarkan pemeriksaan klinis dan mikroskopis, yang memerlukan waktu yang cukup lama, kurang sensitif dan spesifik. Berdasarkan hal tersebut maka dalam penelitian ini dikembangkan uji molekuler real time PCR (rPCR) yang lebih sensitif dan spesifik. Uji rPCR telah berhasil dioptimasi dengan kemampuan deteksi minimum DNA 6,55 copy/μl dan tidak bereaksi silang dengan mikroorganisme yang diuji pada penelitian ini. Dibandingkan dengan uji mikroskopis, uji rPCR memberikan hasil positif 20% lebih tinggi daripada uji mikroskopis. Uji rPCR dapat mendeteksi P.jiroveciipada sampel klinis sputum dan sputum induksi dari pasien HIV dengan pneumonia denganjumlah sel CD4+> 200 maupun ≤ 200. Oleh karena itu, uji rPCR yang telah dioptimasi dalam studi ini dapat mendeteksi P.jirovecii pada sampel klinis sputum dan sputum induksi dari pasien HIV dengan pneumonia dengan jumlah sel CD4+> 200 maupun ≤ 200. Kata Kunci : real time PCR, HIV, pneumocystis jirovecii.